Back Cover: MnxOy/NC and CoxOy/NC Nanoparticles Embedded in a Nitrogen‐Doped Carbon Matrix for High‐Performance Bifunctional Oxygen Electrodes (Angew. Chem. Int. Ed. 32/2014). Issue 32 (1st July 2014) - Masa, Justus; Xia, Wei; Sinev, Ilya; Zhao, Anqi; Sun, Zhenyu; Grützke, Stefanie; Weide, Philipp; Muhler, Martin; Schuhmann, Wolfgang
<x xml:space="preserve">Abstract</x> Dual function oxygen‐reduction and oxygen‐evolution catalysts are vital for the realization of rechargeable metal–air batteries and unitized regenerative fuel‐cell systems. In their Communication on page 8508 ff., W. Schuhmann, M. Muhler et al. report exceptionally active bifunctional catalysts for oxygen‐reduction and ‐evolution based on Co, Mn, and Ni oxides embedded in nitrogen‐doped carbon, which outperform archetypical Pt, Ir, and Ru‐based catalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>